Dinamika Ekonomi Pagang Gadai Dalam Perspektif Ekonomi Syariah: Analisis Manfaat, Kerugian, Dan Keadilan Bagi Pihak Penggadai Dan Penerima Gadai - ahmad lutfi; Rizal Fahlefi (Economics and Digital Business Review, 2025)
This study aims to analyze the economic dynamics of the pagang gadai practice in Minangkabau through an Islamic economic perspective, focusing on its benefits, disadvantages, and fairness for both the mortgagor and the mortgagee. The pagang gadai phenomenon, which has been practiced across generations, demonstrates a gradual shift from a mutual-help mechanism to an economic instrument that often generates unequal distribution of benefits. This research employs a Systematic Literature Review (SLR) approach based on 15 selected articles relevant to fiqh muamalah, customary economic systems, and the governance of mortgage contracts. The review process follows the PRISMA 2020 method with thematic analysis conducted using NVivo 12 software, resulting in four major themes: benefit imbalance, social commercial disparity, weak customary governance, and the potential application of a rahn ijarah contract model based on maqasid principles. The findings reveal that the economic benefit imbalance between mortgagors and mortgagees arises due to ambiguous contract structures, the absence of a clear redemption period, and disproportionate benefit extraction. From the maqasid al-shariah perspective, these conditions violate the principles of hifz al-māl (protection of wealth) and ʿadl (justice). This study proposes a gradual resolution concept through taswiyah of the existing contracts as a phase of restoring economic rights, followed by a renewal process utilizing a fair and productive rahn ijarah contract model. These findings emphasize that reconstructing economic justice in pagang gadai practices must begin with restoring proportional benefits and clarifying contractual structures, rather than focusing solely on legal adjustments. This research contributes to the development of community-based Islamic economics by bridging customary values and maqasid principles within the framework of socio-economic equilibrium in local societies.